Seeing the Atakkae Traditional House: Education, Tourism, Economic and Government Policy Perspectives in Its Development - Maspawaty Tokang; Jackson Yumame; Sriyono; Ilham (Journal of Educational Analytics, 2023)
This study aims to see the Atakkae traditional house from the perspectives of tourism, economy, education, and government policies in its development. The method used is a type of library research through text and discourse analysis by moving the field setting into the library space. The results of this study indicate that, from an educational perspective, the existence of the Atakkae traditional house is often used as a venue for holding various educationally nuanced events, such as exhibitions, cultural performances, and folk arts. Through this event, micro, small, and medium enterprises (MSMEs) can sell their products. Including the development of the Atakkae traditional house tourism will have an impact on the development of other economic sectors. As a closing note, even though the Atakkae traditional house area is one of the favorite tourist attractions in Wajo Regency, the current conditions require attention from the government in caring for and maintaining these cultural and tourism assets.